Runoff Losses in Nitrogen and Phosphorus From Paddy and Maize Cropping Systems: A Field Study in Dongjiang Basin, South China - Zeng, Feifan; Zuo, Zheng; Mo, Juncheng; Chen, Chengyu; Yang, Xingjian; Wang, Jinjin; Wang, Yi; Zhao, Zhongqiu; Chen, Tianyi; Li, Yongtao; Zhang, Zhen; Hu, Zheng; et al. (Frontiers in Plant Science, 2021)
Abstract: Surface runoff is one of predominant routes for agricultural nitrogen (N) and phosphorus (P) losses. Yet their characteristics and corresponding control measures are not fully understood. In 2019-2020, field-scale plot experiments were performed in Dongjiang Basin in South China to investigate the characteristics of N and P runoff losses from paddy and maize cropping systems. Our results showed that N and P losses from maize fields via surface runoff (27.85 and 1.24 kg ha-1 yr-1) were significantly higher than those from paddy fields (15.37 and 0.80 kg ha-1 yr-1). The main forms of N losses were nitrate (NO3--N) and ammonium (NH4+-N) in paddy and maize fields, respectively, whereas particulate P form predominated in surface runoff losses from both paddy and maize fields. Considerable proportions of agricultural N and P (70-80% of the total runoff loss) were lost during basal fertilization and first topdressing application. Moreover, frequent rainfall events following fertilizer application triggered N and P losses from the monitored fields. About 26.22% and 37.48% of N fertilizer were recovered from grains and straw of paddy and maize, respectively, whereas only 12.35% and 19.51% of P fertilizer were recovered during crop harvesting stage. Surface runoff was one of dominant liquid pathways of N loss, whereas most of P loss (introduced from fertilizers without crops utilization) was fixed in soil. Principal component analysis proved that the primary sources of N and P losses were fertilizers rather than N and P in the soil. The current results suggest that controlled management relating to fertilization, irrigation, and tillage strategies are effective measures for reducing N and P losses, thereby controlling agricultural non-point source pollution. It is hoped that this study provides comprehensive field-based inputs on characteristics of N and P runoff losses and formulating appropriate control strategies to protect aquatic environments from eutrophication.